2013
DOI: 10.1002/qua.24447
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical study of enantiomeric and geometric control in chiral guanidine-catalyzed asymmetric 1,4-addition of 5H -oxazol-4-ones

Abstract: Density functional theory calculations are used to study the reaction mechanism and origins of high stereoselectivity in chiral guanidine-catalyzed asymmetric 1,4-addition of 5H-oxazol-4-ones. The reaction involves proton abstraction of 5H-oxazol-4-one, CAC bond formation, and proton transfer. N1 atom of chiral guanidine exchanges its character as base and acid to activate 5H-oxazol-4-one and to facilitate the product formation. The role of N2AH2 is not only H-bond donor for 5H-oxazol-4-one but also electron a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 52 publications
(61 reference statements)
1
6
0
Order By: Relevance
“…Theoretical investigation of the catalytic Michael addition of azlactone and 5 H ‐oxazol‐4‐one to methyl propiolate showed that the Z/E diastereoselectivity of the products is also controlled by the relative orientation of the catalyst and the Michael donor. In view of this, we explored a third route also, which involved attack of 1‐methylpiperazine ( 3 a ) on methyl propiolate from the side opposite to the complexing amine molecule (Figure ).…”
Section: Resultssupporting
confidence: 76%
“…Theoretical investigation of the catalytic Michael addition of azlactone and 5 H ‐oxazol‐4‐one to methyl propiolate showed that the Z/E diastereoselectivity of the products is also controlled by the relative orientation of the catalyst and the Michael donor. In view of this, we explored a third route also, which involved attack of 1‐methylpiperazine ( 3 a ) on methyl propiolate from the side opposite to the complexing amine molecule (Figure ).…”
Section: Resultssupporting
confidence: 76%
“…Lu and Wang have studied the mechanistic aspects of guanidine catalyzed asymmetric 1,4‐addition of 5 H ‐oxazol‐4‐ones to alkynyl carbonyl compounds based on the original experimental finding of Misaki and co‐workers (Scheme 9). [35] The reaction mechanism and origin of high enantioselectivity were investigated by Density Functional Theory (DFT) calculations. The catalytic reaction involves three major steps: (i) deprotonation of methylene group of 5 H ‐oxazol‐4‐one by chiral guanidine base, (ii) C−C bond formation via the addition of an active nucleophile to the terminal carbon of alkynyl carbonyl, (iii) finally, proton transfer to α‐carbon of alkynyl carbonyl intermediate from the protonated catalyst (Figure 4).…”
Section: 4‐addition Reactionsmentioning
confidence: 99%
“…[1,2] Accordingly,s tereochemical control involving facial recognition of both the prochiral enolate (enantiocontrol) and the intermediary allenic enolate (olefin geometry control) in this bond-forming process poses an important yet difficult challenge. [6,7] However, most of the existing methods are restricted to reactions with terminal alkynes.O nly af ew successful examples of stereoselective Michael additions to internal alkynes are known to date,a nd they specifically deal with dialkyl acetylene dicarboxylates as the acceptor. [6,7] However, most of the existing methods are restricted to reactions with terminal alkynes.O nly af ew successful examples of stereoselective Michael additions to internal alkynes are known to date,a nd they specifically deal with dialkyl acetylene dicarboxylates as the acceptor.…”
Section: Conjugate Addition Of Enolates (Original Michael Addition)mentioning
confidence: 99%